IMPACT OF STRATEGIC PLANNING ON THE MANAGEMENT OF WATER UTILITY OPERATORS (OOA) IN MEXICO - Rodriguez-Rios, Rigoberto; Mayett-Moreno, Yésica (Seven Editora, 2026)
This study analyzes the impact of strategic planning on the management of Water Utilities (WU) in Mexico and its importance for improving operational and financial efficiency, as well as the sustainability of the service. Through the application of an instrument to 21 WU in the state of Sonora and other states, a significant association was identified between the size of the WU and the adoption of strategic tools (p